Enterprise Architecture Patterns For Online Transportation - Huyearka Usady; Teduh Dirgahayu (Syntax Idea)
Online transportation is an internet-based service where passengers can order transportation via a platform. Gojek and Grab are one of the largest platforms in Southeast Asia and dominate the online transportation market share. However, platform development generally only focuses on value creation and stakeholder regulation without considering information technology (IT) services. In practice, enterprise architecture (AE) has an important role in IT-business strategy alignment. An enterprise architect can use the AE Pattern concept to provide effective solutions when developing enterprise systems. Organizations that do not implement enterprise patterns will produce poor solution targets. Therefore, the importance of implementing the AE pattern in aligning business-IT and the lack of practice related to the AE pattern. This research uses various kinds of modeling to be able to produce AE Patterns for online transportation. The purpose of this research is to model AE patterns on business and data on online transportation. The results of the AE pattern modeling are evaluated by making a prototype design then testing with the UAT method and producing using cases/processes that are successful or appropriate.